Reflective Teacher Supervision Through Videos of Classroom Teaching (2015)
The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed their pedagogical actions through videos became more reflective and self-evaluative, as they provided a deeper analysis regarding their practice. With collaborative supervision, teacher candidates can be encouraged to recognize and understand the complexities of language learning and teaching both locally and globally.El objetivo de este trabajo es presentar diferentes roles de profesor supervisor según modelos distintos y destacar la importancia de diálogos colaborativos con apoyo de grabaciones de video. Para lograrlo, se muestran resultados de un estudio cualitativo desarrollado en un curso de formación de profesores de inglés como lengua extranjera en Brasil. Los resultados indicaron que la supervisión colaborativa fue eficiente frente a la adversidad de contextos educativos. Se concluyó que los estudiantes-profesores que observaron sus acciones pedagógicas a través de videos se volvieron más reflexivos y lograron autoevaluarse, ya que hacían un profundo análisis de su práctica. Con supervisión colaborativa, se alienta a futuros profesores a reconocer y comprender las complejidades de la enseñanza y aprendizaje local y globalmente.